Late onset autosomal dominant Charcot– Marie–Tooth 2 neuropathy in a Costa Rican family - Berghoff, Corinna (2009)
Objective: To describe the clinical, electrophysiologic and morphologic features of a Costa Rican family with an autosomal dominant inherited Charcot–Marie–Tooth (CMT) neuropathy. Methods: The field study took place in Costa Rica, Central America. Seven patients underwent neurological examinations and standard electrodiagnostic tests, and a sural nerve biopsy was taken from one patient. Fifteen family members were screened for gene defects associated with CMT disease. Results: Characteristic features of this family were a late age of onset (35–56 years), positive sensory symptoms and muscle cramps. Based on electrodiagnostic and morphologic data, the patients were classified as having a CMT2 neuropathy. The CMT1A duplication/HNPP deletion and point mutations in genes PMP22, MPZ, Cx32 and EGR2 implicated in the most common types of CMT disease were excluded. Subsequently, almost all known CMT loci were excluded by linkage analysis. Discussion: Features of this family were a late age of onset and positive sensory symptoms. This new autosomal dominant CMT neuropathy is associated with an unknown gene defect. [Neurol Res 2009; 31: 283–288]